Economic impacts of melting of the Antarctic Ice Sheet - Dietz, Simon (Zenodo, 2022)
Dataset supporting figures and tables in Dietz, Simon and Koninx, Felix (forthcoming), "Economic impacts of melting of the Antarctic Ice Sheet", Nature Communications